Peran Pemerintah Desa Terhadap Pengembangan Badan Usaha Milik Desa Monano Kecamatan Karamat Kabupaten Buol - Moh Yani J Baingan; Usman Moonti; Melizubaida Mahmud; Syarwani Canon; Sudirman Sudirman (State University of Gorontalo, 2023)
This study aimed to discover the Role of the Village Government in the Development of Village-Owned Enterprises (BUMDes) in Monano Village, Karamat Sub District, Buol Regency, Central Sulawesi Province. This study used a quantitative approach with a descriptive quantitative method, a correlational design, and a sample of 30 people. Meanwhile, the data were collected through observations, questionnaires, interviews, and documentation and the analyzed using Multiple Linier Regression analysis. In accordance with the finding, it is concluded that the Village Government has played a role in developing Village-Owned Enterprises (BUMDes) in Monano Village, Karamat Sub District, Buol Regency, Central Sulawesi Province.